Synthesis and Crystalline Structure of Zinc Complexes with Antihypertensive Drug Lisinopril - Márcia C. de Souza; Luan F. Diniz; Chris H. J. Franco; Renata Diniz (Journal of Chemistry)
The structural investigation of Zn2+ complexes with the ligand lisinopril (LIS), an inhibitor of angiotensin-converting enzyme (ACE), was performed. The main objective is to compare if Zn-LIS coordination in vitro is similar to that observed in vivo. Two zinc complexes were obtained from different synthetic routes. The synthesis of LISZn1 used stirring, while for LISZn2 involved solvothermal conditions, which favoured the full deprotonation of lisinopril ligand. In this sense, the different synthetic routes resulted in the formation of complexes with notorious chemical and structural differences. The crystal structure of LISZn2 showed that the ligand is coordinated to Zn2+ ion by oxygen and nitrogen atoms which is different from that observed in vivo. In vitro, the coordination of lisinopril occurs only by an oxygen atom of the central carboxylate group. LISZn2 forms a one-dimensional (1D) coordination polymer and presents disorder atoms in its unit cell.